Effect of thyroxine on munc-18 and syntaxin-1 expression in dorsal hippocampus of adult-onset hypothyroid rats - Y. Zhu; D. Ning; F. Wang; C. Liu; Y. Xu; X. Jia; D. Zhu (European Journal of Histochemistry, 2012)
Adult-onset hypothyroidism induces a variety of impairments on hippocampus- dependent neurocognitive functioningin which many synaptic proteins in hippocampus neurons are involved. Here, we observed the effect of adult-onset hypothyroidism on the expression of syntaxin-1 and munc-18 in the dorsal hippocampus and whether the altered proteins could be restored by levothyroxine (T4) treatment. All rats were separated into 4 groups randomly: hypothyroid group, 5μg T4/100 g body weight (BW) treated group, 20 μg T4/100g BW treated group and control group. The radioimmunoassay kits were applied to assay the levels of serum T3 and T4, and the levels of syntaxin-1 and munc-18 in hippocampus were assessed by immunohistochemistry and Western blot. Both analysis corroborated that syntaxin-1 in the hypothyroid group was significantly higher. Munc-18 was lower in four layers of CA3 and dentate gyrus by immunohistochemistry. After two weeks of treatment with 5 μg T4/100g BW for hypothyroidism, syntaxin-1 levels were completely restored, whereas the recovery of munc-18 only located in two of the four impaired layers. Twenty μg T4/100g BW treatment normalized munc-18 levels. These data suggested that adult-onset hypothyroidism induced increment of syntaxin-1 and decrement of munc-18 in the dorsal hippocampus, which could be restored by T4 treatment. Larger dosage of T4 caused more effective restorations.